2012
DOI: 10.4132/koreanjpathol.2012.46.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Difficulties in Fine Needle Aspiration of Benign Salivary Glandular Lesions

Abstract: BackgroundThe diagnostic accuracy of fine needle aspiration cytology (FNAC) of salivary lesions is relatively high, but cytologic interpretation might be confusing if the sample is lacking typical cytologic features.MethodsThere were 77 cases of benign salivary lesions, consisting of pleomorphic adenoma (PA) in 61 cases, Warthin's tumor (WT) in 12 cases, and other benign lesions in 4 cases. The causes of the discrepancies between the FNAC and the histologic diagnoses were evaluated.ResultsMajor discrepancies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Recognition of aspiration sites and the correlation with radiologic findings are important, and a detailed cytologic examination based on both typical and non-typical cytologic features will be needed [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition of aspiration sites and the correlation with radiologic findings are important, and a detailed cytologic examination based on both typical and non-typical cytologic features will be needed [10].…”
Section: Resultsmentioning
confidence: 99%
“…There were no differences in sensitivity, but specificity and the positive predictive values were higher in the benign salivary gland lesions while the negative predictive value was higher in malignant lesions. Brennan et al reported differences in the sensitivity and specificity between initial FNAC and repeated FNAC as 70 and 93 and 84 and 95 %, respectively [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine needle aspirations are a simple and common way to obtain a pathologic diagnosis of these tumors, and studies have shown accuracy to be 77.8% (12), with similar results to frozen section (13). Nevertheless, errors can be reported in sampling and interpretation (14) and in those cases, further surgical exploration is warranted. We found that 30% of those patients who underwent FNA prior to parotidectomy had indeterminate results.…”
Section: Cancer Investigationmentioning
confidence: 80%
“…Even though, previous studies showed that multiple lesions, smoking and olderly male are helpful to suggest WTs, there are still many overlapping features are confusing and difficult to diagnosis and claify before operation [3][4][5] . Fine needle aspiration (FNA) is considered to be gold standard for parotid tumors diagnosis, but has some limitations, even under optimum conditions and may be associated with poor levels of diagnostic accuracy [6] . In addition, a meta-analysis study [7] showed the actual sensitivity for parotid tumors diagnosis by using FNA was estimated to be low (only 71%).…”
Section: Introductionmentioning
confidence: 99%